Smoking and Hormesis as Confounding Factors in Radiation Pulmonary Carcinogenesis - Charles L. Sanders; Bobby R. Scott (SAGE Publishing, 2008)
Confounding factors in radiation pulmonary carcinogenesis are passive and active cigarette smoke exposures and radiation hormesis. Significantly increased lung cancer risk from ionizing radiation at lung doses < 1 Gy is not observed in never smokers exposed to ionizing radiations. Residential radon is not a cause of lung cancer in never smokers and may protect against lung cancer in smokers. The risk of lung cancer found in many epidemiological studies was less than the expected risk (hormetic effect) for nuclear weapons and power plant workers, shipyard workers, fluoroscopy patients, and inhabitants of high-dose background radiation. The protective effect was noted for low- and mixed high- and low-linear energy transfer (LET) radiations in both genders. Many studies showed a protection factor (PROFAC) > 0.40 (40% avoided) against the occurrence of lung cancer. The ubiquitous nature of the radiation hormesis response in cellular, animal, and epidemiological studies negates the healthy worker effect as an explanation for radiation hormesis. Low-dose radiation may stimulate DNA repair/apoptosis and immunity to suppress and eliminate cigarette-smoke-induced transformed cells in the lung, reducing lung cancer occurrence in smokers.